2008
DOI: 10.1103/physrevb.78.134101
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiocalculations of the thermodynamics and phase diagram of zirconium

Abstract: The finite-temperature density-functional theory and quasiharmonic lattice dynamics are used to calculate the Gibbs free energy and quasiharmonic phonons of the hexagonal-close-packed ͑hcp͒ and omega ͑͒ crystal structures for Zr. The hcp phonon dispersions agree with experiment; the phonon dispersions have not been measured yet. From the free energy, the volume thermal expansion coefficients of ␣-Zr are predicted. The calculated volume thermal expansion coefficients for ␣-Zr are in good agreement with the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
(30 reference statements)
7
23
0
Order By: Relevance
“…This shows that our DFT-PAW calculation correctly reproduces experimental finding [37,38] that αZr is the most stable ground state phase at zero temperature and pressure, with total energy 96.485 J/mole lower than ωZr. This result also matches previous DFT calculations using both FPLMTO [39] and PAW [40]. However, previous calculations by Bajaj et al [41] found the energy of αZr to be about 1 kJ/mole higher than ωZr.…”
Section: Zrsupporting
confidence: 91%
“…This shows that our DFT-PAW calculation correctly reproduces experimental finding [37,38] that αZr is the most stable ground state phase at zero temperature and pressure, with total energy 96.485 J/mole lower than ωZr. This result also matches previous DFT calculations using both FPLMTO [39] and PAW [40]. However, previous calculations by Bajaj et al [41] found the energy of αZr to be about 1 kJ/mole higher than ωZr.…”
Section: Zrsupporting
confidence: 91%
“…If one can obtain the free energies of different phases within quasi-harmonic approximation (QHA), the phase boundary can be calculated by comparing the difference of the free energies. In our previous work [20], we only obtained the phase boundary of a-and x-Zr within QHA.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic transfer between the broad sp band and the much narrower d band in group IV transition metals is a likely driving force behind structural transitions [9] and has stimulated a large number of molecular dynamic investigations that explore the changes in bonding [10][11][12][13].…”
mentioning
confidence: 99%